The development of body representations in school-aged children. Issue 4 (2nd October 2021) - Raimo, Simona; Iona, Teresa; Di Vita, Antonella; Boccia, Maddalena; Buratin, Stefano; Ruggeri, Francesco; Iosa, Marco; Guariglia, Cecilia; Grossi, Dario; Palermo, Liana
Abstract: Following the triadic taxonomy, three different body representations do exist, namely the body semantics, the body structural representation and the body schema. The development of these body representations has been widely investigated in toddlers, but several issues remain to be addressed in school age. To assess age- and gender-related changes in different body representations and to investigate the presence of different patterns of interplay between these representations of the body, 90 children (age range: 7–10) and 37 young adults (age range: 18–35) were given tasks assessing the body semantics, the body structural representation and the body schema as well as control tasks. The present results suggested that the body schema, evaluated by means of hand laterality judgments, was still not completely developed in school-aged children, whereas the body structural representation reached an adult-like pattern by the age of 9–10 years. Finally, body semantics was fully developed in school-aged children. These findings were discussed in terms of their theoretical implications, for a better understanding of body representation development; also, implications for clinical assessment of body representation disorders were discussed.